Predicting factors of aggression among Indonesian middle adolescents with conduct problems in the community: A correlational study - Saputra, Fauzan; Uthis, Penpaktr; Suktrakul, Sunisa (Belitung Nursing Journal, 2025)
Background: Middle adolescents with conduct problems (CP) are at higher risk for aggression than their peers. However, factors contributing to this phenomenon remain insufficiently understood, particularly in Indonesia. Objective: This study aimed to examine the direct and indirect relationships among parental monitoring, self-esteem, self-control, peer deviance, media violence exposure, academic self-concept, and aggression, using Problem Behavior Theory and supported literature review as a conceptual framework. Methods: A cross-sectional correlational design was employed. Data were collected from May to June 2023 from students aged 14 to 16 years with CP across nine junior high schools in Aceh Province, Indonesia. Instruments included the Parental Monitoring Instrument, Rosenberg Self-Esteem Scale, Brief Self-Control Scale, Deviant Peer Scale, Extended Content-Based Media Exposure Scale, Academic Self-Concept Questionnaire, and Aggression Problem Behavior Frequency Scale Adolescent Rating. Data were analyzed using path analysis with LISREL 8.80 and the Sobel test. Results: A total of 423 students participated in the study. Self-control and peer deviance were directly associated with aggression (z = -1.93, β = -0.19, and z = 2.41, β = 0.35, p <0.05, respectively). Self-esteem showed an indirect association with aggression, mediated by self-control (z = -1.783, β = -0.795, p = 0.038). Peer deviance mediated the effects of parental monitoring and media violence exposure on aggression (z = 2.126, β = 1.020, p = 0.017, and z = 2.14, β = 1.055, p = 0.017, respectively). The model explained 42 percent of the variance in aggression. Conclusion: The findings highlight the importance of regular screening for conduct problems and aggression by community nurses and school-based counseling teachers, as well as the development of interventions focusing on peer deviance and self-control, which were identified as the most significant predictors of aggression.